The Effect of Two Somatic-Based Practices Dance and Martial Arts on Irisin, BDNF Levels and Cognitive and Physical Fitness in Older Adults: A Randomized Control Trial - Hola, Veronika; Polanska, Hana; Jandova, Tereza; Jaklová Dytrtová, Jana; Weinerova, Josefina; Steffl, Michal; Kramperova, Veronika; Dadova, Klara; Durkalec-Michalski, Krzysztof; Bartos, Ales (Clinical interventions in aging, 2024)
BACKGROUND: Maintaining healthy brain function during ageing is of great importance, especially for the self-sufficiency of older adults. The main aim of this study was to determine the effects of dance and martial arts on exerkines Brain Derived Neurotrophic Factor (BDNF) and irisin blood serum levels. METHODS: This randomized controlled trial examined the effects of dance and martial arts on serum Brain-Derived Neurotrophic Factor (BDNF) and irisin levels, as well as cognitive function, mood, and physical measures in older adults. Seventy-seven independently living older adults (mean age 70.3±3.8 years) were randomized into three groups: dance (DG), martial arts (MaG), and control (CG), followed over 12 weeks. Generalized linear models were used to assess the interventions' effects. RESULTS: There was a significant increase in BDNF levels in both the DG (1.8 ± 4.9, p < 0.05) and MaG (3.5 ± 6.3, p < 0.05), while CG experienced a decrease (-4.9 ± 8.2, p < 0.05). Between-group effects were significant for BDNF, with DG and MaG showing higher levels than CG (p < 0.05). No significant changes in irisin levels were found. Cognitive performance, particularly attention and mental flexibility (measured by the Trail Making Test A and B), significantly improved in the DG compared to CG (p < 0.05). Additionally, participants in DG showed improved mood based on the Geriatric Depression Scale (p < 0.05) compared to CG. Anthropometric T-scores were significantly associated with changes in irisin levels (p < 0.05) after intervention. CONCLUSION: The study found that dance and martial arts upregulated BDNF levels, with dance showing notable improvements in cognitive function and mood in older adults. Changes in anthropometric measures were linked to increased irisin levels. These findings suggest that both dance and martial arts may promote healthy brain function in aging populations. TRIAL REGISTRATION: NCT05363228.
Keywords: senioři; fibronektiny; Male; Female; Aged; bojové sporty; afekt; tanec; Brain-Derived Neurotrophic Factor; ageing; Physical Fitness; mužské pohlaví; tělesná výkonnost; biomarkers; ženské pohlaví; mozkový neurotrofický faktor; kognice; cognitive performance; Dancing; Martial Arts; Fibronectins; cognitive domains; cognitive function; Cognition; lidé; Humans; Affect; serum